2018
DOI: 10.1111/1365-2435.13045
|View full text |Cite
|
Sign up to set email alerts
|

Plant functional groups regulate soil respiration responses to nitrogen addition and mowing over a decade

Abstract: Nitrogen (N) deposition and land‐use practice (e.g. mowing) could have profound effects on soil respiration. However, the changes in other ecosystem components, such as plant functional groups (PFGs), may control soil carbon (C) efflux response to long term global change. A 10‐year (2005–2014) field experiment was conducted with both N addition (10 g N m−2 year−1) and mowing (once a year) in a northern Chinese temperate grassland. We collected continuous data on soil respiration over 10 years accompanied with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 60 publications
4
47
0
Order By: Relevance
“…As a common facility in CO 2 manipulation experiments (Hungate et al 1997;Langley & Megonigal 2010), OTCs used in the present study may create a high temperature and high humidity microenvironment compared with the ambient climate, likely modulating grassland responses to rising atmospheric CO 2 concentrations (Obermeier et al 2017). In addition, although our previous studies at this experimental site have demonstrated that mowing could not change N addition effects on grassland plant community and soil respiration (Yang et al 2012;Du et al 2018), this study conducted in a fenced grassland might fail to investigate possible roles of grazing and mowing, the two common grassland use practices, in regulating grassland responses to CO 2 enrichment, especially under complex climate change scenarios. Thus, caution should be taken when extrapolating our findings to the regional scale or managed grasslands.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…As a common facility in CO 2 manipulation experiments (Hungate et al 1997;Langley & Megonigal 2010), OTCs used in the present study may create a high temperature and high humidity microenvironment compared with the ambient climate, likely modulating grassland responses to rising atmospheric CO 2 concentrations (Obermeier et al 2017). In addition, although our previous studies at this experimental site have demonstrated that mowing could not change N addition effects on grassland plant community and soil respiration (Yang et al 2012;Du et al 2018), this study conducted in a fenced grassland might fail to investigate possible roles of grazing and mowing, the two common grassland use practices, in regulating grassland responses to CO 2 enrichment, especially under complex climate change scenarios. Thus, caution should be taken when extrapolating our findings to the regional scale or managed grasslands.…”
Section: Discussionmentioning
confidence: 83%
“…; Du et al . ), this study conducted in a fenced grassland might fail to investigate possible roles of grazing and mowing, the two common grassland use practices, in regulating grassland responses to CO 2 enrichment, especially under complex climate change scenarios. Thus, caution should be taken when extrapolating our findings to the regional scale or managed grasslands.…”
Section: Discussionmentioning
confidence: 99%
“…Abiotic control is proposed to be associated with the constrained effect of decreased pH on microbial biomass, SOM decomposition, and turnover under N addition (Averill & Waring, 2017;Du et al, 2018;Ye et al, 2018). In a conceptual model proposed by Averill and Waring (2017), the response of soil C progress with N addition is relative with the changes in soil acidity.…”
Section: Abiotic Control and Aggregate Formationmentioning
confidence: 99%
“…Previous studies have focused on above‐ and below‐ground net primary production, plant diversity, and carbon cycling responses to N addition in juvenile and adult stage plants (Du et al, ; Humbert, Dwyer, Andrey, & Arlettaz, ; Pakeman et al, ; Soons et al, ; Yang et al, ). Many studies have shown that long‐term N addition affects offspring performance, such as seed germination, seedling establishment, and soil seed banks (Basto et al, ; Li, Hou, Song, Yang, & Li, ; Xia & Wan, ).…”
Section: Introductionmentioning
confidence: 99%
“…With the current increases in N deposition, quantifying the potential responses of plant communities to increased N availability is critical for assessing future vegetation trajectories through climate-plant feedback (Isbell et al, 2013;Luo, Sherry, Zhou, & Wan, 2009). Previous studies have focused on above-and below-ground net primary production, plant diversity, and carbon cycling responses to N addition in juvenile and adult stage plants (Du et al, 2018;Humbert, Dwyer, Andrey, & Arlettaz, 2016;Pakeman et al, 2016;Soons et al, 2016;Yang et al, 2012). Many studies have shown that long-term N addition affects offspring performance, such as seed germination, seedling establishment, and soil seed banks (Basto et al, 2015;Li, Hou, Song, Yang, & Li, 2017;Xia & Wan, 2013).…”
mentioning
confidence: 99%